Bisection of the X chromosome disrupts the initiation of chromosome silencing during meiosis in Caenorhabditis elegans - Yisrael Rappaport (Nature Portfolio, 2021)
During meiosis, sex chromosomes show silenced gene expression that is disrupted when translocated to autosomes. Here, the authors engineer C. elegans with bisected X chromosomes and see active transcription in gonads, indicating continuity of sex chromosomes promotes silencing.